Spillover Effects and Supranational Parliaments: The Case of Mercosur - Malamud, Andrés (2016)
‘Spillover’ refers to the inner dynamics whereby the members of a regional scheme feel compelled to either enlarging the scope or increasing the level of their mutual commitments or both. It is promoted by actions crystallized into institutions, whose performance creates demand for further action and incremental institution-building. In the case of the EU, the institutions commonly acknowledged as greatest ‘spillover promoters’ are the Commission, the Court, and the European Parliament; in Mercosur there are no functional equivalents to the two former institutions yet, but a common Parliament (Parlasur) has been established and is often purported as a potential engine of integration. This paper addresses its structure and performance in order to assess whether it has produced, or may produce, some kind of spillover by either fostering new regional dynamics or cajoling national governments into upgrading their commitments to the region.